Study of the lower limp's angle during weightlifting exercises using an accelerometer-based system (2014)
This article describes the implementation and use of a two-accelerometer system to measure the angle formed between lower joints of weightlifters during the execution of the technical gesture. Being aware of movement between joints will allow identifying bad moves and prevent injuries in athletes. Likewise, it will help in turn to rehabilitation for people with problems in the movement of their joints. This design is based on open platforms both hardware and software. The preliminary result shows that we can connect a two-accelerometer system with an error in the measure of the angle no greater than 1.3% (0.795% on average). © 2014 IEEE.